Body's perceptions of elderly women in a physical activity program Cambios en la percepción del cuerpo de mujeres de edad avanzada, a través de un programa de actividad física - P. Silva; C. Novais; P. Botelho-Gomes; J. Carvalho (Asociación Española de Ciencias del Deporte, 2011)
The aim of the study is to know elderly women’s body perceptions and the importance of a multicomponent physical activity program. Semi-structured interviews and focus groups were conducted in 19 elderly women. Data were subjected to an interpretative analysis after the treatment of the information (QSRNVivo7). Before the PA program, data suggested social representations of the female body: weakened body; functional limitations; sickness. These women seek PA program because they expect body improvements: functional independence; health; physical appearance. After PA program they perceived some changes related to their mobility; better capacity to cope with chronic disease and counter with advancing age; and also physical repositioning of identities. In this way, physical activity program can be considered as a valid instrument for body empowerment, an “independent” and “healthy” body, i.e., weakened body recovers a certain social significance and repositions itself in the society. Key Words: women, physical activity, body El objetivo de este estudio es conocer la percepción del cuerpo de las mujeres en edad avanzada antes y después de un programa multicomponente de actividad física. Los datos de las entrevistas, semiestructuradas y de grupo, a 19 ancianas se sometieron a un análisis interpretativo tras el tratamiento de la información (QSRNVivo7). Antes del programa de actividad física, los datos reflejan representaciones sociales de un cuerpo envejecido y frágil (con dolores y limitaciones funcionales). Estas mujeres buscan la actividad física por razones relacionadas con la independencia funcional y con la salud, y también con la apariencia física. Tras el programa, las mujeres percibieron un cuerpo más ágil, capaz de controlar el dolor y detener el avance de la edad. Las mujeres identifican la actividad física como un instrumento importante para mantenerse independientes, saludables y para el dominio del propio cuerpo; el cuerpo envejecido recupera una cierta importancia social. Palabras Clave:mujeres, actividad física y deportiva, cuerpo